Value of Character and Philosophy of Life KH. Ahmad Dahlan - Nana Sutarna; Agus Saeful Anwar (ISTAWA, 2020)
This study aims to explore the value of character and philosophy of life of the founder of Muhammadiyah (KH. Ahmad Dahlan). The research method used is library research. The primary data source is the philosophy of the teachings of KH. Ahmad Dahlan, and the secondary sources are other books that are relevant and relevant to the research. Analysis of the data used in this study is the Content analysis method. The author's findings relate to the question that KH. Ahmad Dahlan bequeathed seven philosophies and his messages, in which teaches to be a visionary human being able to think ahead that is to be happy in the world and the hereafter. Character Value is exemplified by him, namely the value of religious character, honesty, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the motherland, valuing achievement, friendly or communicative, peace-loving, fond of reading social care and responsibility. The character education of KH. Ahmad Dahlan can support government character education so that it becomes an active character education.Penelitian ini bertujuan untuk menggali nilai karakter dan falsafah hidup pendiri Muhammadiyah (KH. Ahmad Dahlan). Metode penelitian yang digunakan adalah penelitian kepustakaan (library research). Sumber data primer adalah falsafah ajaran KH. Ahmad Dahlan, sumber sekundernya adalah buku-buku lain yang bersangkutan dan relevan dengan penelitian. Analisa data yang digunakan dalam penelitian ini adalah metode content analysis. Temuan penulis berkaitan dengan pertanyaan yang ada bahwa KH. Ahmad Dahlan mewariskan tujuh falsafah dan pesan-pesan beliau, yang di dalamnya mengajarkan supaya menjadi manusia yang visioner mampu untuk berfikir kedepan yaitu supaya dapat bahagia dunia dan akherat. Nilai Karakter yang dicontohkan oleh beliau yakni nilai karakter religius, jujur, disiplin, kerja keras, kreatif, mandiri, demokratis, rasa ingin tahu, semangat kebangsaan, cinta tanah air, menghargai prestasi, bersahabat atau komunikatif, cinta damai, gemar membaca, peduli sosial, dan tanggungjawab. Adapun pendidikan karakter KH. Ahmad Dahlan dapat mendukung pendidikan karakter pemerintah sehingga menjadi pendidikan karakter yang efektif.